Effect of diffuse pollution on water quality in mountain forest streams - García, Adriana Karina (2017)
Agriculture is the main source of surface and groundwater pollution. It increases suspended solids and organic matter concentration with the subsequent eutrophication. Citrus and sugarcane are the predominant crops in the subtropical area under study and the agrochemicals used in different periods of the year. This study was carried out taking into consideration main regional drivers as well as precipitation regime (seasonal rains) and ground conditions. Two monitoring sites were established: one that reflected conditions not affected by agricultural activities (upper watershed) and another affected by agricultural diffuse pollution (downstream) in the middle of the watershed. The Seco and Famaillá rivers show the effects of diffuse pollution caused by land use. There is a differential impact in river water quality that depends on the proportion of altered basins, riparian forest and kind of crop. Even though the measured physicochemical variables do not go beyond the established limits to be classified as contaminants, these monitoring stations are useful in the determination of water variations due to diffuse pollution. Evidences of riparian forests benefits mitigating effects of agricultural use of the soil were observed.